Imaging diagnosis of probable osteomyelitis in a 9-month-old infant from prehistoric Brazil: a brief history of healthcare in ancient times - Monge Calleja, Álvaro M. (2025)
Individual 9, a 9 ± 3-month-old infant from the Middle-Holocene (6,650-6,170 years BP) found in Toca do Enoque rock-shelter in Piauí, Brazil, showed significant pathological bone changes and received exceptional mortuary treatment. Previous studies indicated administration of normative parental care and non-normative healthcare, although the differential diagnosis remained vague. This study reexamines the paleopathological diagnosis using X-rays, CT scans, and 3D reconstructions of 10 long bones. Pathological changes included endocranial bone growths and polyostotic, bilateral, and asymmetrical periosteal new bone formation (PNBF) affecting long bones and ribs. The right tibia was the most affected, showing an anteromedial deformity and inside out-perforations with burred, jagged edges. Imaging revealed Harris lines in the left humerus, endosteal bone proliferation in the tibiae, humeri, and right radius, and loss of cortical density in the right tibia. A direct connection between the medullary, subperiosteal, and external spaces suggested characteristics of cloacae or subperiosteal abscesses. Tibial changes suggest an involucrum formation without signs of sequestra, consistent with acute, hematogenous neonatal/infantile osteomyelitis (OM). Although extremely rare, cloacae can arise at early ages under specific circumstances, such as chronic neonatal/infant OM. Delayed pus evacuation, coupled with breastfeeding, resilience, and healthcare may have extended Individual 9’s lifespan and the duration of the infection. This possible case of neonatal/infantile OM is rare and valuable, potentially the youngest documented in Paleopathology and the first in the Americas. However, nonspecific costal and endocranial lesions do not rule out the presence of comorbidities. Expanding the corpus of case studies is essential for refining diagnoses in bioarcheological and paleopathological research.